2023
DOI: 10.3390/su15118503
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Technology in Physical Education Teaching in the Wake of the Pandemic

Abstract: Physical education is seen as an essential subject for the development of healthy habits and well-being, in line with Sustainable Development Goal 3. Furthermore, the impact of technology on all aspects of life is now an undeniable reality. The field of education is no exception, and digitalisation has undoubtedly been accelerated by the emergency situation resulting from the COVID-19 pandemic. This paper aims to analyse the scientific production related to the field of physical education, technology, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…A study analyzed the role that technology played during the COVID-19 pandemic, concluding that it was very useful in conducting physical education classes, and that even in the post-pandemic era it continues to be so [36] . Similarly, another study mentions the importance of technology during the pandemic in physical education classes, highlighting that after this episode, we must move into a "new era" with innovative ideas, including technology [52,53] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study analyzed the role that technology played during the COVID-19 pandemic, concluding that it was very useful in conducting physical education classes, and that even in the post-pandemic era it continues to be so [36] . Similarly, another study mentions the importance of technology during the pandemic in physical education classes, highlighting that after this episode, we must move into a "new era" with innovative ideas, including technology [52,53] .…”
Section: Discussionmentioning
confidence: 99%
“…Given the above information, it is of utmost relevance that educational communities consider gamification as an alternative to improve the levels of motor development and involvement in the practice of physical activity of their students, thinking about how useful this methodology was during the COVID-19 pandemic [36] and also that we are in post pandemic times and students are even more involved with technology. Specifically in Chile, there is not much evidence that relates the variables gamification and motor development, so its study in our region becomes a necessity.…”
Section: Introductionmentioning
confidence: 99%
“…In the modern era, technology that has been used in sev-eral sectors such as physical education (Jastrow et al, 2022;Marín-Suelves et al, 2023;Ridwan et al, 2023;Zulkifli & Danis, 2022), health (Baashar et al, 2023;Kan Yeung et al, 2021;Rodríguez-Abad et al, 2021;Seals et al, 2021), busi-ness (Capasa et al, 2022;Rauschnabel et al, 2022), sports (Badau et al, 2023;Pu & Yang, 2022;Witte et al, 2022) encountered a significant increase in several countries. Data showed that using technology could provide benefit, which can help athletes to achieve their goals optimally (Jumareng et al, 2021;Jumareng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, trends such as the rapid spread of physical activity using non-face-to-face remote systems [1,2], the verification of health promotion and treatment effects [3,4], and the convergence of physical activity and information and communications technology (ICT) have been observed [5][6][7]. After the pandemic, a new popular trend called "EdTech" appeared [8][9][10].…”
Section: Introductionmentioning
confidence: 99%